2013
DOI: 10.1136/thoraxjnl-2013-203576
|View full text |Cite
|
Sign up to set email alerts
|

The five-repetition sit-to-stand test as a functional outcome measure in COPD

Abstract: BackgroundMoving from sitting to standing is a common activity of daily living. The five-repetition sit-tostand test (5STS) is a test of lower limb function that measures the fastest time taken to stand five times from a chair with arms folded. The 5STS has been validated in healthy community-dwelling adults, but data in chronic obstructive pulmonary disease (COPD) populations are lacking. Aims To determine the reliability, validity and responsiveness of the 5STS in patients with COPD. Methods Test-retest and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
279
7
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(308 citation statements)
references
References 40 publications
13
279
7
9
Order By: Relevance
“…However, up to now, there has been no consensus on the optimal method to estimate the MCID. 42,43 Furthermore, the ROC curve method, using external anchor measures, was successfully used to calculate the MCID of the Clinical COPD Questionnaire 44 and of the 5-repetition sit-to-stand test 45 in subjects with COPD. We acknowledge that the lack of control group may be a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to now, there has been no consensus on the optimal method to estimate the MCID. 42,43 Furthermore, the ROC curve method, using external anchor measures, was successfully used to calculate the MCID of the Clinical COPD Questionnaire 44 and of the 5-repetition sit-to-stand test 45 in subjects with COPD. We acknowledge that the lack of control group may be a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Forced Expiratory Volume in one second (FEV 1 ) and forced vital capacity (FVC) were assessed by spirometry, breathlessness using the Medical Research Council (MRC) dyspnea scale [17] and comorbidities recorded using the age-adjusted Charlson Index [18]. Functional measures included quadriceps maximum voluntary contraction (QMVC) [19], 4-m gait speed (4MGS) [20], 5-repetition sit-to-stand (5STS) [21] and incremental shuttle walk (ISW) [22]. Health-related quality of life was assessed using the St Georges Respiratory Questionnaire (SGRQ) [23] and the COPD Assessment Test (CAT) [24,25].…”
Section: Additional Measurementsmentioning
confidence: 99%
“…One advantage of this test is that it does not present a learning effect, and can therefore 372 be performed just once 7 in Table 4. 32 Mesquita et al 31 Horie et al 20 Beauchamp et al 29 Butcher et al 19 n= 85 (34.3±13.6%) n=95 (33 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] To stand up from a chair and walk 3 meters at usual speed, turn and walk back to the chair and sit down again.…”
mentioning
confidence: 99%
“…Beauchamp et al demonstrated that the test could discriminate fallers from non-fallers; the test 246 duration was 3.1 seconds longer in fallers compared with non-fallers 30 . Moreover, longer time to complete the TUG test at baseline and after 1-year follow-up period were 248 predictors of deterioration in disease related health status 33 .Sit-to-stand test: Fifteen studies which used the STS test to evaluate lower limb functionality were found7,18,19,[21][22][23][35][36][37][38][39][40][41][42][43] . The protocols vary greatly(Table 1), including differences in chair height, which ranged from 40 to 48 cm7,22,[35][36][37][38][39][40][41][42] or was adjusted to…”
mentioning
confidence: 99%